Increased risk of IgE-mediated allergies in patients with celiac disease: a case-control study - Azhati, Ahemalali; Xue, Shenglong; Shi, Tian; Guan, Mengmeng; Kong, Wenjie; Feng, Yan; Ma, Xin; Ayerken, Aliya; Gao, Feng (Frontiers in Nutrition, 2026)
BackgroundCeliac disease (CeD) is an autoimmune small intestinal disorder frequently associated with allergic diseases. However, the prevalence, allergen differences, and clinical characteristics of allergic reactions in adult CeD patients remain unclear.ObjectiveThe primary aim of this study, conducted primarily in the Chinese population, is to determine the prevalence and clinical characteristics of patients with CeD who have concomitant allergies.MethodsA total of 92 CeD patients diagnosed between June 2018 and June 2025 and 184 healthy subjects matched for age and gender were enrolled. Allergen profiles were evaluated in both CeD patients and healthy controls to compare the prevalence of allergies and differences in major allergens between the two groups. A retrospective analysis of clinical data and medical records from 92 patients with CeD was performed to further explore the clinical characteristics, prevalence of allergic comorbidities, and endoscopic Marsh classification features in patients with CeD who had and did not have allergies.ResultsThe prevalence of IgE-mediated allergies in CeD patients was 58.7% (54/92), which was significantly higher than that in healthy controls (24.5%, 45/184) (P < 0.05). Allergen testing showed that the dominant allergens in CeD patients included milk, beef, wheat flour, and dog epithelium. Additionally, among the CeD patients, the prevalence of allergic rhinitis was 2.17% (2/92), allergic asthma was 1.09% (1/92), and atopic dermatitis was 5.43% (5/92). Compared with CeD patients without comorbid allergies, those with allergies had a significantly lower body mass index (BMI) (22.89 ± 5.21 vs. 20.92 ± 4.21 kg/m2, P < 0.05) and a substantially higher incidence of diarrhea (15.79% vs. 38.89%, P < 0.05). No significant differences were found between the two groups in terms of gender distribution, tissue transglutaminase IgA (tTg-IgA) levels, or Marsh classification.ConclusionThe results of this study demonstrate that the prevalence of IgE-mediated allergies in patients with CeD is significantly higher than that in the healthy population. Importantly, comorbid allergies may exacerbate intestinal malabsorption and worsen digestive symptoms (specifically diarrhea) in CeD patients. Based on these findings, allergen screening is strongly recommended for CeD patients presenting with severe malabsorption or refractory diarrhea.